EFEKTIFITAS PENGGUNAAN SURAT PERNYATAAN TANGGUNG JAWAB MUTLAK (SPTJM) DALAM RANGKA PERCEPATAN PENINGKATAN CAKUPAN KEPEMILIKAN AKTA KELAHIRAN DI SUKU DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA ADMINISTRASI JAKARTA BARAT (Lex Jurnalica, 2023)
AbstractThe issuance of the Minister of Home Affairs Regulation Number 9 of 2016 concerning the Acceleration of Increasing the Coverage of Birth Certificate Ownership as revoked based on the Minister of Home Affairs Regulation Number 108 of 2019 concerning Implementing Regulations of Presidential Regulation Number 96 of 2018 concerning Requirements and Procedures for Population Registration and Civil Registration and Ministerial Regulations Domestic Affairs Number 109 of 2019 concerning Forms and Books Used in Population Administration allows for a Statement of Absolute Responsibility (SPTJM) to be made as a substitute for supporting documents that do not exist or are not found in the making of a birth certificate. This innovation was carried out to make it easier for residents to get public services in the field of population administration, especially in the management of birth certificates. Juridically, this allows the issuance of birth certificates which contain the phrase "whose marriage has not been registered in accordance with statutory regulations". This recording will certainly have an impact on the status of civil relations between children and parents. The East Jakarta Administration City Population and Civil Registry Sub-agency does not have data on requests for issuance of birth certificates using the SPTJM, both the SPTJM for correctness of birth data and the SPTJM for correctness as husband and wife. The existing data only shows the number of birth certificate holders. The status of the civil relationship between the child and the parents from the birth certificate issued on the basis of the SPTJM can be assumed that the position of the child is the same as that of a child born to a legally married couple. Keywords: statement of absolute liability, birth certicate  AbstrakLahirnya Peraturan Menteri Dalam Negeri Nomor 9 Tahun 2016 tentang Percepatan Peningkatan Cakupan Kepemilikan Akta Kelahiran sebagaimana telah dicabut berdasarkan Peraturan Menteri Dalam Negeri Nomor 108 Tahun 2019 tentang Peraturan Pelaksnaan Peraturan Presiden Nomor 96 Tahun 2018 tentang Persyaratan Dan Tata Cara Pendafatran Penduduk dan Pencatatan Sipil serta Peraturan Menteri Dalam Negeri Nomor 109 Tahun 2019 tentang Formulir dan Buku Yang Digunakan Dalam Administrasi Kependudukan memungkinkan dibuatnya Surat Pernyataan Tanggung Jawab Mutlak (SPTJM) sebagai pengganti dokumen penunjang yang tidak ada atau tidak ditemukan dalam pembuatan akta kelahiran.  Inovasi ini dilakukan untuk mempermudah penduduk mendapatkan pelayanan publik di bidang administras kependudukan khususnya dalam pengurusan akta kelahiran.  Secara yuridis hal ini memungkinkan terbitnya akta kelahiran yang terdapat frasa “yang perkawinannya belum tercatat sesuai dengan peraturan perundang-undangan”.  Pencatatan ini tentu akan berdampak terhadap status hubungan keperdataan antara anak dan orang tua.  Suku Dinas Kependudukan dan Catatan Sipil Kota Administrasi Jakarta Timur tidak memiliki data permohonan penerbitan akta kelahiran yang menggunakan SPTJM, baik SPTJM kebenaran data kelahiran maupun SPTJM kebenaran sebagai pasangan suami istri.  Data yang ada hanya menunjukkan jumlah kepemilikan akta lahir. Status hubungan keperdataan antara anak dan orang tua dari akta kelahiran yang terbit berdasarkan SPTJM dapat diasumsikan bahwa kedudukan anak tersebut sama dengan kedudukan anak yang lahir dari pasangan kawin yang sah. Kata Kunci: Surat Pernyataan Tanggung Jawab Mutlak (SPTJM), Akta Kelahiran